DESAIN PENGEMBANGAN PEMBELAJARAN INTERAKTIF PENDIDIKAN AGAMA ISLAM BERBASIS MACROMEDIA FLASH 8 - Devia Hidayah Aninda; Istikomah Istikomah (PAI RAFAH, 2023)
Technological developments in the digital era continue to advance rapidly and are utilized by all lines including the world of education. Many applications that can be utilized by teachers in learning activities include Macromedia Flash 8. This is very helpful in making it easier for students to learn and can make it easier for educators to deliver learning materials. For this reason, educators are required to have the creativity and ability to implement technology-based interactive learning in Islamic Religious Education. The purpose of this research is to develop an interesting and innovative interactive learning design so that students can be enthusiastic about learning Islamic Religious Education materials. The research method used in this research is qualitative with the Research and Development (R&D) approach of the 4D model proposed by Thiagarajan. The subjects in this research were 11 students of Antatika High School class XI MIPA for the limited collab test and 25 students of Antarctica High School class XI IPS for the field collab test. The analysis and validation stage carried out by experts was carried out first, then continued at the stage of testing the product to be developed. The results obtained are learning media based on Macromedia flash 8 on Islamic Religious Education material is very feasible to use because of its attractive appearance and not monotonous.